Cruise report CAGE15-3 - Silyakova, Anna; Serov, Pavel; Jansson, Pär; Gründger, Friederike; Niemann, Helge; Graves, Carolyn; Arnadottir, Erna O.; Linke, Peter; Frank, Carsten; Rubinke, Oliver; Pohlman, John; Boze, Lee-Gray; et al. (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
The cruise had two main objectives: Deployment of the two CAGE ocean floor observatories (OS1 and OS2) at shallow PKF site and deeper PKF site; CAGE ocean floor observatories were designed and build as collaborative work of CAGE scientists with Kongsberg engineers. Observatories have identical set up except that only one of them have side looking multibeam. The set up is: Seabed Platform/seabed lander/mooring frame (x2) – OS1 has black mooring frame, OS2 has grey mooring frame, CTD (x2), Oxygen sensor (x2), CH4 sensor (x2), CO2 sensor (x2), pH sensor (x1), Fluorometer (x2), ADCP (x2), Current profiler (x1), Multibeam echosounder (x1) – grey lander, OS2, Broadband Hydrophone (x2), Flowmeter (x2) For specific description of each lander, please refer to ‘taking over’ documents (WP4 team leader). Landers and sensors arrived to Tromsø with a track from Hamburg, A. Silyakova was a reference person to receive goods and shipping documents. Time period between 24 and 26 of June was the assemblage of observatories and tests of telemetry/communication/camera on a launcher. Pär Jeanson (PhD student WP4) and Reidar Kaasa (substitute engineer instead of Anoop in WP4) from CAGE were assigned to receive training on observatory assemblage/communication. 26 of June – taking over procedure. Sites for the deployment were discussed during preparatory phase. Water depth at the sites could not exceed 500 meters due to restrictions in relation to the recovery rope, which is only 500 meters long. Photographs from the tow cam used during CAGE 15-2 cruise (chief scientist on the cruise G. Panieri) revealed sites with bacterial mats on the ocean floor. Prior each deployment we did echosounder and multibeam survey to know where flares are highly concentrated. Information from the survey was mapped instantly. Target spots for both observatories were chosen based on all this combined information. Oceanographic survey in the area of shallow PKF methane flares; From the “Testing seep fertilization hypothesis” proposal:‘ During cruise CAGE 14-1 the USGS-GAS system detected elevated methane fluxes near the coast and over the shelf seep site in ca. 90m water depth. Methane fluxes above the 240 and 400m site are much less, although slightly elevated with respect to the open ocean (e.g. Vestnesa). Unexpectedly, high methane concentrations (up to 20nM) are often accompanied by low CO2 concentrations. Initial estimates of the total CO2 budget show that under those conditions seep areas are CO2 sinks. What are the biological, geochemical and hydrographic conditions that made these seeps a CO2 sink? Are the observations from CAGE 14-1 repeatable? And ultimately, what are the processes causing the strong CO2 consumption.’It was decided to test seep fertilization hypothesis during CAGE 15-3 cruise by conducting comprehensive water sampling for biogeochemical environment in the entire water column above the area of methane flares. At the same time, USGS-GAS system was onboard allowing to simultaneously measuring surface water/lower atmosphere gas concentrations. This potentially allows calculating vertical gas flux from one realm to another. Depending on available time, collaborators equipment and human resources, water from 64 CTD stations was samples for following parameters: CH4 concentration; discrete sampling to introduce into CDRS system – 13C CH4, CO2; pH; DIC and 13C DIC; DOC; MOx; FISH; DNA; DMSP; CDOM; Nutrients (nitrate, silicate, phosphate). The cruise may be known as: CAGE15_3